Detection of the electromechanical delay and its components during voluntary isometric contraction of the quadriceps femoris muscle - Begovic, Haris; Zhou, Guang-Quan; Li, Tianjie; Wang, Yi; Zheng, Yong-Ping (Frontiers in Physiology, 2014)
Electromechanical delay (EMD) was described as a time elapsed between first trigger and force output. Various results have been reported based on the measurement method with observed inconsistent results when the trigger is elicited by voluntary contraction. However, mechanomyographic (MMG) sensor placed far away on the skin from the contracting muscle was used to detect muscle fiber motion and excitation-contraction (EC) coupling which may give unreliable results. On this basis, the purpose of this study was to detect EMD during active muscle contraction whilst introducing an ultrafast ultrasound (US) method to detect muscle fiber motion from a certain depth of the muscle. Time delays between onsets of EMG-MMG, EMG-US, MMG-FORCE, US-FORCE and EMG-FORCE were calculated as 20.5 ± 4.73 ms, 28.63 ± 6.31 ms, 19.21 ± 6.79 ms, 30.52 ± 8.85 ms and 49.73 ± 6.99 ms, respectively. Intrarater correlation coefficient (ICC) was higher than MMG when ultrafast US was used for detecton of the Δt EMG-US and Δt US-FORCE, ICC values of 0.75 and 0.70, respectively. Synchronization of the ultrafast ultrasound with EMG and FORCE sensors can reveal reliable and clinically useful results related to the EMD and its components when muscle is voluntarily contracted. With ultrafast US, we detect onset from the certain depth of the muscle excluding the tissues above the muscle acting as a low - pass filter which can lead to inaccurate time detection about the onset of the contracting muscle fibers. With this non-invasive technique, understanding of the muscle dynamics can be fascilitated.